Re-engineered and integrated industrial relations model for governance integrity : multiple case studies in Bangladesh - Andalib, Tarnima Warda; Mohd Ridzuan, Darun (KnE Social Sciences, 2019)
This paper re-engineers the ‘industrial relationships between the leaders and the employees (RLE)’ model in the Bangladeshi manufacturing companies, where labour management, supply, and demand of workflow and workers, employee’s conditions and rights are significant factors. Researchers have pondered the ‘industrial relationships between leaders and employees’ component as part of ‘human resource management’ and have adept the integration by using soft systems technology, where this component’s codes are associated with employees’ rights protocols of ‘Universal declaration of human rights (UDHR), ‘International labour organisations (ILO) and ‘Bangladesh labour act 2006’ (BDL). Here, qualitative method’s multiple case studies are applied with purposeful sampling to choose twelve cases (12) and eighty-seven (87) participants’ for in-depth interviews, which are transcribed and coded methodically in NVIVO. Here, re-engineered ‘industrial relationships between leaders and employees model’ is the outcome. The concept of integration is novel, which is an addition to the knowledge of literature and the advancement of ‘industrial relationships between leaders and employees’ model.